PENGARUH PECKING ORDER HYPHOTHESIS PADA EMITEN PERUSAHAAN MAKANAN DAN MINUMAN GO PUBLIC DI BURSA EFEK INDONESIA - , Harri Priyono, S. Sos; , Prof. Dr. Eduardus Tandelilin, MBA, CWM ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objectives of this study was examine pecking order theory in food and beverages industries in Indonesia. Additionally, it is specifically focused on investigating the influence of tangibility ratio, Profitability, Growth, Firm Size and Debt to Total Assets of the past variables to leverage in food and beverages the companies during the period 2005-2009. This study used 18 samples of stock in food and beverages industries that have completed and audited financial statement during the period of 2005-2009. This study applied the method of hypothesis testing with multiple linear regression analysis model, and the classical assumptions. The results showed that the ratio of Profitability and Debt to Total Assets past significant effect on leverage, while the ratio of tangibility, Growth, and Firm Size no significant effect on leverage. The result shows that there is an indication of pecking order theory contribution in the financial decisions process among the food and beverages companies within the Indonesian stock market.